Molecular targeted photoimmunotherapy for HER2-positive human gastric cancer in combination with chemotherapy results in improved treatment outcomes through different cytotoxic mechanisms. Issue 1 (December 2016) - Ito, Kimihiro; Mitsunaga, Makoto; Arihiro, Seiji; Saruta, Masayuki; Matsuoka, Mika; Kobayashi, Hisataka; Tajiri, Hisao
Abstract Background Photoimmunotherapy (PIT) is a novel type of molecular optical imaging-guided cancer phototherapy based on a monoclonal antibody conjugated to a photosensitizer, IR700, in combination with near-infrared (NIR) light. PIT rapidly causes target-specific cell death by inducing cell membrane damages and appears to be highly effective; however, we have previously demonstrated that tumor recurrences were eventually seen in PIT-treated mice, likely owing to inhomogeneous mAb-IR700 conjugate distribution in the tumor, thus limiting the effectiveness of PIT as a monotherapy. Here, we examined the effects of human epidermal growth factor-2 (HER2)-targeted PIT in combination with 5-fluorouracil (5-FU) compared to PIT alone for HER2-expressing human gastric cancer cells. Methods NCI-N87 cells, HER2-positive human gastric cancer cells, were used for the experiments. Trastuzumab, a monoclonal antibody directed against HER2, was conjugated to IR700. To assess the short-term cytotoxicity and examine the apoptotic effects upon addition of 5-FU in vitro, we performed LIVE/DEAD and caspase-3 activity assays. Additionally, to explore the effects on long-term growth inhibition, trypan blue dye exclusion assay was performed. NCI-N87 tumor xenograft models were prepared for in vivo treatment studies and the tumor-bearing mice were randomized into various treatment groups. Results Compared to PIT alone, the combination of HER2-targeted PIT and 5-FU rapidly induced significant cytotoxicity in both the short-term and long-term cytotoxicity assays. While both 5-FU and/or trastuzumab-IR700 conjugate treatment induced an increase in caspase-3 activity, there was no additional increase in caspase-3 activity upon NIR light irradiation after incubation with 5-FU and/or trastuzumab-IR700. The combination of HER2-targeted PIT and 5-FU resulted in greater and longer tumor growth inhibition than PIT monotherapy in vivo. This combined effect of PIT and 5-FU is likely owing to their different mechanisms of inducing tumor cell death, namely necrotic membrane damage by PIT and apoptotic cell death by 5-FU and trastuzumab. Conclusions PIT in combination with 5-FU resulted in enhanced antitumor effects compared to PIT alone for HER2-expressing human gastric cancer in vitro and in vivo. This combination photoimmunochemotherapy represents a practical method for treating human gastric cancer and should be investigated further in the clinical setting.